MORAL AND EDUCATIONAL VALUES IN THE NOVEL “THREE CUPS OF TEA” BY GREG MORTENSON - Nuke Nugraha Cahyawati (Universitas Indraprasta PGRI, 2021)
Abstract: The purpose of the research is to find out: 1) the moral values contained in the true story of Greg Mortenson. 2) Educational values provided by Greg Mortenson. The research method used in this study is qualitative with a structural approach. The study results are: 1) The moral values in the novel Three Cups of Tea by Greg Mortenson and David Oliver Relin are caring 26.9%, friendly 15.4%, helpful 11.5%, brave 11.5%, hardworking 19.2%, and optimistic 15.4%. The most moral value in the data is caring with 7 data or 26.9%. 2) The educational values contained in the novel Three Cups of Tea by Greg Mortenson and David Oliver Relin are attitudes toward the world of education amounting to 28.6% and the struggle to establish schools 71.4%. The most data found in the struggle to establish schools amounted to 71.4%.Keywords: moral values, educational values, content analysis